Characteristics of indicators of sustainable development - Кошеленко, Світлана Василівна; Карюк, Діана (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2016)
The article reveals the notion of sustainable development. The main criterion for the selection of indicators which has been considered is their important characteristics which are necessary for the establishment of a national assessment of informative system and the dynamics of sustainable development of the state. It is determined that the main characteristics of indicators are the following: possibility of quantitative measurement and comparison, compliance with international indicators of sustainable development and existence of additional specific indicators.